Combined Cornus Officinalis and Paeonia Lactiflora Pall Therapy Alleviates Rheumatoid Arthritis by Regulating Synovial Apoptosis via AMPK-Mediated Mitochondrial Fission - Huang, Lichuang; Hu, Shaoqi; Shao, Meiyu; Wu, Xin; Zhang, Jida; Cao, Gang (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that leads to cartilage destruction and bone erosion. In-depth exploration of the pathogenesis of RA and the development of effective therapeutic drugs are of important clinical and social value. Herein, we explored the medicinal value of Cornus officinalis Sieb. and Paeonia lactiflora Pall. in RA treatment using a rat model of collagen-induced arthritis (CIA). We compared the therapeutic effect of Cornus officinalis and Paeonia lactiflora with that of their main active compounds, ursolic acid and paeoniflorin, respectively. We demonstrated that the combination of Cornus officinalis and Paeonia lactiflora effectively inhibited the release of factors associated with oxidative stress and inflammation during RA, therein ameliorating the symptoms and suppressing the progression of RA. We further showed that the underlying mechanisms may be related to the regulation of apoptosis in synovial tissues, and we investigated the potential involvement of AMPK-mediated mitochondrial dynamics in the therapeutic action of the two drugs and their active components.